Pro-biomics: Omics Technologies To Unravel the Role of Probiotics in Health and Disease. Issue 5 (24th February 2021) - Kiousi, Despoina Eugenia; Rathosi, Marina; Tsifintaris, Margaritis; Chondrou, Pelagia; Galanis, Alex
Abstract: The comprehensive characterization of probiotic action has flourished during the past few decades, alongside the evolution of high-throughput, multiomics platforms. The integration of these platforms into probiotic animal and human studies has provided valuable insights into the holistic effects of probiotic supplementation on intestinal and extraintestinal diseases. Indeed, these methodologies have informed about global molecular changes induced in the host and residing commensals at multiple levels, providing a bulk of metagenomic, transcriptomic, proteomic, and metabolomic data. The meaningful interpretation of generated data remains a challenge; however, the maturation of the field of systems biology and artificial intelligence has supported analysis of results. In this review article, we present current literature on the use of multiomics approaches in probiotic studies, we discuss current trends in probiotic research, and examine the possibility of tailor-made probiotic supplementation. Lastly, we delve deeper into newer technologies that have been developed in the last few years, such as single-cell multiomics analyses, and provide future directions for the maximization of probiotic efficacy. Abstract : High-throughput, multiomics platforms provide invaluable insights into the beneficial effects of probiotic supplementation on the host, setting the stage for personalized, tailor-made interventions.